THE EFFECT OF THE INTERNATIONAL STANDARD BIBLIOGRAPHIC DESCRIPTION (MONOGRAPHS) ON CATALOG RECORDS / LES EFFETS DE LA DESCRIPTION INTERNATIONALE NORMALISES SUR LES FICHES - Packer, Katherine H. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see pdf